Poland - Environmental and Social Safeguards : Use of Country System - World Bank (Washington, DC, 2013)
The main objective of the assessment is to determine how Poland's environmental and social safeguard systems can be used in place of the corresponding Bank safeguards, at sector, sub-national, or country level, and how it will apply to current and future Bank-financed operations in Poland. This assessment will be done through a safeguard diagnostic review which involves: (i) an equivalence analysis, to determine if the Poland legal and regulatory systems are equivalent to the corresponding World Bank's safeguards; and (ii) an acceptability assessment, to assess Poland's level of institutional capacity, procedures, and performance to implement its own safeguard systems, and identify gap filling measures as appropriate. Moreover, given the European Union's (EU's) convergence policy and requirements of the EU acquis communautaire which apply to all member states, the assessment is also expected to provide further insight and guidance on extending the use of country systems to other countries with active World Bank investment portfolios. The report is organized in three parts. Part one presents the objectives of the assessment, background information on the World Bank's policy on the use of environmental and social safeguard country systems, as well as Poland's legal and regulatory framework for environmental management and protection which includes obligations under the EU acquis communautaire, and the methodology used. Part two focuses on the findings of the equivalence analysis, and part three presents the findings from the acceptability assessment. The concluding section summarizes the main recommendations and next steps.